Implementation of Sharia Maqashid in Household Financial Management: A Study on Women Members of the Aisyiyah Ponorogo Regional Leadership - Nisa, Evilia Khoirun; Hartono , Arif; Rois , Adib Khusnul (Maaliyah: Journal of Islamic Economic Law and Islamic Finance, 2025)
This study examines the implementation of Maqashid Syariah principles in household financial management, focusing on women members of the Ponorogo Aisyiyah Regional Executive (PDA). The goal is to analyze financial practices, evaluate the application of Maqashid Sharia, and identify the role of Aisyiyah membership. This study uses a phenomenological qualitative approach by collecting primary data through in-depth interviews and observations of seven key informants who were purposively selected. The researcher analyzed the data through the stages of reduction, presentation, and conclusion verification. Key findings revealed that members implemented strategic financial management and aligned with the five goals of Maqashid Sharia. They diversify sources of income, prioritize spending (basic needs, religion, education), and invest in sharia instruments such as gold and land. The study also identifies mechanisms for operationalizing religious principles, such as the "logistics of faith" where religious obligations become a fixed budget post. Further analysis shows a model of collaborative financial stewardship between husband and wife and the strategy of building "layered resilience" through a combination of tangible and intangible assets. However, participants faced a "digital-sharia dilemma", which is the challenge of maintaining financial discipline in the era of digital consumerism. In conclusion, the principles of Maqashid Syariah have proven to be operationalized in household financial management, although contemporary Islamic financial literacy education is needed to answer digital challenges. This study recommends a follow-up study with a mixed-methods approach to explore the dynamics of the integration of the five aspects of hifz in maqashid sharia more comprehensively.